Occurrence of enterococci in raw pork and beef and their antibiotics multiresistance - Miroslav Kročko; Margita Čanigová; Viera Ducková (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2008)
The aim of this study was to determine the microbial contamination of raw pork and beef, to estimate the prevalence of enterococci and investigate the antibiotic multiple resistance of enterococci. Total bacterial counts (TBC) were cultured on Plate count agar and enterococci count were cultured on Slanetz – Bartley agar. The TBC after 24 h post mortem reached the value 3.61 ± 0.78 log cfu . cm−2 for pork and 2.58 ± 0.63 log cfu . cm−2 for beef. The count of enterococci after 24 h post mortem reached the value 1.98 ± 1.29 log cfu . cm−2 for pork and 1.16 ± 0.47 log cfu . cm−2 for beef. The average value of TBC in pork and beef were significantly (P < 0.05) higher after 7 days of ripening at 4 °C storage than 24 h post mortem and in pork and beef reached the value 4.69 ± 1.46 log cfu . cm−2 and 4.32 ± 1.44 log cfu . cm−2 resp. The average values of enterococci count after 7 days of ripening in pork and beef were 2.00 ± 1.27 log cfu . cm−2 and 0.84 ± 0.80 log cfu . cm−2 resp. Susceptibilities of isolated enterococci from pork to antimicrobial agents were tested using the disc diffusion method. Enterococcus faecium was the predominat species out of 50 isolates recovered from pork (72%), followed by E. faecalis (10%). Other enterococcal isolates were identified sporadically (E. mundtti–8%, E. spp.–10%). Out of 50 isolates of enterococci 14% were resistant to vancomycin and 10% were resistant to erythromycin, 18% to ampicillin, 24% to gentamicin and 34% to tetracycline. The calculated antibiotic code profiles indicated that large proportion of enterococci were resistant to all tested antibiotics except vancomycin. Our study suggests that raw pork and beef play a potential role as reservoirs of enterococci multiresistant to antibiotics.